2019
DOI: 10.1177/0886260519839422
|View full text |Cite
|
Sign up to set email alerts
|

“Change Really Does Need to Start From Home”: Impact of an Intimate Partner Violence Prevention Strategy Among Married Couples in Nepal

Abstract: Approximately 54% of women in rural Nepal report lifetime physical or sexual violence. The Change Starts at Home project is a primary prevention strategy to reduce and prevent marital intimate partner violence (IPV). This study analyzed in-depth interviews with 17 married couples (n = 34 individuals) at intervention midline and end line. Case-based analysis and thematic summaries were used to assess change, couple concordance, and gendered reporting patterns at midline. Individual changes included husband's al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The Change trial did find that frequent LDG attendance was associated with decreases in many types of IPV, some of which persisted to endline. The benefits of the intervention concur with findings from the qualitative LDG cohort which found sustained changes in labor roles, communication, decision-making, alcohol abuse, roaming, conflict resolution, and experience of IPV within the cohort (McGhee et al, ). Study findings also concur with another recently conducted trial in Rwanda involving couples and communities which found couple-related improvements in IPV that went through an intensive, 6 month curriculum but no impact in the community sample in response to activism based activities (Chatterji, Stern, Dunkle, & Heise, 2019 under review).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The Change trial did find that frequent LDG attendance was associated with decreases in many types of IPV, some of which persisted to endline. The benefits of the intervention concur with findings from the qualitative LDG cohort which found sustained changes in labor roles, communication, decision-making, alcohol abuse, roaming, conflict resolution, and experience of IPV within the cohort (McGhee et al, ). Study findings also concur with another recently conducted trial in Rwanda involving couples and communities which found couple-related improvements in IPV that went through an intensive, 6 month curriculum but no impact in the community sample in response to activism based activities (Chatterji, Stern, Dunkle, & Heise, 2019 under review).…”
Section: Discussionsupporting
confidence: 75%
“…If the respondent reported either 2 or 3, she was considered to have participated in decisions regarding sexual activity. Decision making regarding financial purchases and sexual decision making were particularly salient themes in mid-intervention qualitative transcripts (McGhee et al, ), so these items were singled out for the endline analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This article is also limited from not reporting dyadic analysis findings, which can beneficially identify particular overlaps and contrasts among couples as partners (Eisikovits & Koren, 2011). Dyadic analysis among couples has been conducted in Rwanda (Stern & Heise, 2018) and Nepal (McGhee, Shrestha, Ferguson, Shrestha, & Clark, 2019). The focus of this article was to unpack broader themes reported among couples, and how this compared between Nepal and Rwanda, and dyadic analysis was outside the scope of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant sociodemographic variables included: current marital status (non-live-in, live-in partner only, married, widow, divorced) and wealth index (low, average, high). Other covariates of interest were selected according to the literature and their possible relationship with IPV; these included: age [ 20 , 21 , 22 ], partner's alcohol consumption [ 23 , 24 , 25 ], both women's and partner's educational levels [ 26 , 27 , 28 ], number of children (0, 1, 2, >2), family history of violence (the father used to beat the mother) [ 9 , 29 ] and geographical region [ 30 , 31 ] (Lima Metropolitan Area, rest of the coastline, highlands, jungle).…”
Section: Methodsmentioning
confidence: 99%